ナンキョク プリンスオラフ エンガン ニ ブンプ スル コショウスイ ノ スイシツ ニツイテ - 平林, 順一; ヒラバヤシ, ジュンイチ; 小坂, 丈予; オサカ, ジョウヨ; HIRABAYASHI, Jun-ichi; OSSAKA, Joyo (国立極地研究所, 1976)
P(論文) 1972年12月から1974年2月にかけて,プリンスオラフ沿岸に点在する7つの露岩地域(新南岩,日の出岬,東オングル島,西オングル島,ラングホブデ,スカルブスネス,スカーレン)に存在する多数の湖沼を中心とした地球化学的調査を行った.93の湖沼について,湖沼水を採取し,主成分の化学分析を行い,それらの成分傾向と,起源について若干の検討を行った.その結果は次の通りである.1)プリンスオラフ沿岸の湖沼は,地形的に現在も氷河が落ち込んでいるもの,海水が直接取り込まれて出来たもの,窪地に融雪水などがたまって出来た湖沼などに分けられる.2)これら湖沼水の総塩分量は6.7mg/l-3.26×10^5mg/lの広範囲にわたっており,特に,ラングホブデ,スカルブスネスには1×10^4mg/l以上の塩湖が多く存在している.その他の地域では1×10^3mg/lをこえる湖沼はほとんど認められない.3)この地域の湖沼水の成分供給源は,海水そのものと,これに加えて風送塩によるものとして考察した. Geochemical researches were carried out for the period from December 1972 to February 1974 on the lake waters in the following seven areas along the Prince Olav Coast Sinnan Rocks, Cape Hinode, East Ongul Island, West Ongul Island, Langhovde, Skarvsnes and Skallen. 93 lake water samples were collected and their major components were analyzed. The following results were obtained with respect to chemical compositions of these lake waters and the origin of their salts : 1) These lakes along the Prince Olav Coast were classified into the following three types according to their topographical origin lakes created by collapse down of extant glaciers, lakes created by the direct invasion of sea waters in the past, and lakes of meteoric waters in depressed ground. 2) Total concentration of salts in these lake waters ranges from 6.7mg/l to 3.26×10^5mg/l. Many high salinity lakes where the total concentration of salts exceeds 1×l0^4mg/l were found in Langhovde and Skarvsnes, whereas, in the other areas few lakes contained more than 1×l0^3mg/l salts. 3) The salts dissolved in these lake waters originate from sea water. The deviations of the chemical composition of the lake waters from that of sea water are ascribed to wind-blown sea spray which affected the chemical composition. departmental bulletin paper